2018
DOI: 10.1177/0091217417749799
|View full text |Cite
|
Sign up to set email alerts
|

Two cases of high serum clozapine concentrations occurring during inflammation in Chinese patients

Abstract: Objective Serious infections or inflammations have been associated with serum clozapine concentration increases and sometimes with clozapine toxicity. Method These two cases describe Chinese patients (Case 1: a 57-year-old female nonsmoker with severe dermatitis and Case 2: a 47-year-old male nonsmoker with influenza and secondary infection). Results In both cases, the Drug Interaction Probability Scale established the presence of a probable drug-drug interaction. In both cases, the clozapine and the total clo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 25 publications
0
19
0
Order By: Relevance
“…A doubling of the concentration was only observed when there was an elevation of the serum C-reactive protein (CRP) and widespread effect on the skin all over the body. 11 In a recent retrospective review of 131 clozapine inpatients at Beijing Anding Hospital, we found 18 episodes of infections/ inflammations in 16 patients. At the total sample level, these episodes: (1) extended for 2% (482/24 789) of clozapine days and (2) contaminated 3% (46/1384) of trough steady-state serum concentrations of clozapine.…”
Section: Inflammation Can Increase Clozapine Levelsmentioning
confidence: 98%
See 3 more Smart Citations
“…A doubling of the concentration was only observed when there was an elevation of the serum C-reactive protein (CRP) and widespread effect on the skin all over the body. 11 In a recent retrospective review of 131 clozapine inpatients at Beijing Anding Hospital, we found 18 episodes of infections/ inflammations in 16 patients. At the total sample level, these episodes: (1) extended for 2% (482/24 789) of clozapine days and (2) contaminated 3% (46/1384) of trough steady-state serum concentrations of clozapine.…”
Section: Inflammation Can Increase Clozapine Levelsmentioning
confidence: 98%
“…10 There are also published clozapine intoxications during severe inflammation without infection. 11 More recently, in a Beijing hospital, three cases of clozapine intoxication we identified included ones with pneumonia, 12 influenza 11 and dermatitis in the absence of infection. 11 In these three Chinese patients severe infections were associated with roughly double the serum concentrations, 11 12 while the effects in relation to dermatitis depended more on its severity.…”
Section: Inflammation Can Increase Clozapine Levelsmentioning
confidence: 99%
See 2 more Smart Citations
“…The mechanism of infection‐related changes in clozapine pharmacokinetics is thought to be related to release of inflammatory cytokines that act as inhibitors of cytochrome P‐450 enzymes 3 , 4 . Two recent case reports discussed the occurrence of elevated serum clozapine concentrations in patients with inflammatory conditions 5 …”
mentioning
confidence: 99%